More Power to You: Securing Central Europeas Future Energy Supply (Global Journal of Human-Social Science, 2012)
Single-track dependency amid dwindling global energy resources has lead to crises such as the one experienced in 2009 when Russia strangled Europe s energy stream as a result of the Ukrainian-Russian gas conflict between Gazprom and Naftohas Ukrainy over supplies prices and debts Past and current crises in the European Union EU -Russia energy relationship reveal the vulnerability of the Visegr dGroup V4 Poland Hungary Slovakia and Czech Republic which are among the most dependent countries within the EU on imports of oil and gas especially since the group s domestic production is largely incapable of meeting the current demands of its own consumers As a result of slow progress with the Nabucco Pipeline expected to be operational by 2017 the South Stream completion due by 2015 and Germany seeking to secure its own energy future with the Nord Stream project V4 countries face the threat of being left out in the cold Europe s renewed interest in energy security is influenced by internal and external factors Internally lack of coherent policy in securing newenergy sources for the V4 collectively as opposed to singular regional states and declining European energy production and fragmented energy markets externally have contributed to skepticism and fear over the V4 s energy future This paper examines the V4 s critical energy security challenges as well as its position within an arena of competition as Russia Norway and Algeria remain the major gas suppliers of Europe for the foreseeable future In addition to critical analyses of both primary and secondary sources a combined methodology of both qualitative and quantitative approaches is employed to assess V4 dependency on a variety of energy sources This paper argues that V4 countries can enhance the security of its collective energy future in two ways 1 the diversification of energy sources and 2 reconsidering its energy policy to make energy security a central pillar wit
Keywords: Energy dialog; Gazprom; infrastructure; pipelines; gas fields